2019
DOI: 10.7567/1882-0786/ab0d32
|View full text |Cite
|
Sign up to set email alerts
|

Top-down fabrication of GaN nano-laser arrays by displacement Talbot lithography and selective area sublimation

Abstract: We show that a 4 μm thick GaN layer grown by metal-organic vapour phase epitaxy can be transformed into a well-organized array of GaN nanowires (NWs) using displacement Talbot lithography and selective area sublimation. The optical quality of the GaN NWs obtained by this method is attested by their room temperature photoluminescence and the observation of lasing under optical pumping with a minimum excitation power density threshold of 2.4 MW cm−2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Sublimation has been recently proposed as a simple top-down route to form nanostructures such as nanorods, nanopyramids, InGaN quantum discs or nanoporous material from GaN-based material without introducing the damage that occurs in dry etching 6163 . By protecting the GaN surface with a thermally resistant dielectric layer and then annealing the sample under vacuum and sufficiently high temperatures, selective area sublimation of GaN can be carried out through the apertures of the mask.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sublimation has been recently proposed as a simple top-down route to form nanostructures such as nanorods, nanopyramids, InGaN quantum discs or nanoporous material from GaN-based material without introducing the damage that occurs in dry etching 6163 . By protecting the GaN surface with a thermally resistant dielectric layer and then annealing the sample under vacuum and sufficiently high temperatures, selective area sublimation of GaN can be carried out through the apertures of the mask.…”
Section: Resultsmentioning
confidence: 99%
“…However, sublimation is sensitive to structural defects 64 , occurs not only vertically but also laterally, and is only suitable for GaN and InGaN materials; not AlGaN with more than 10% Al 65 . Therefore, although promising for photonic applications and the nanostructuring of GaN materials 62,63,65,66 , ICP dry etching provides more flexibility on the type of materials that can be patterned and on the nanostructure profile.…”
Section: Resultsmentioning
confidence: 99%
“…The NWs are produced by employing nano-patterning techniques such as lithography (optical and e-beam) [25,86,87], nanosphere based patterning [88,89], laser interference lithography [90,91], etc. The etching could be done using dry plasma process [92,93] or acid based wet chemical etching [25,86,87,91]. Dry etching methods have merits such as high precision, uniformity over wafer scale, scalability etc., but they could also lead to stress generation due to high energy plasma and isotropic lateral etching issues.…”
Section: Top-down Approachmentioning
confidence: 99%
“…However, the process was reported to be strongly sensitive to threading defects, resulting in the formation of pores under the mask and, therefore, with a poor organization of nanoholes overall and poor uniformity of the nanohole dimensions. More recently, Damilano and co-authors reported several works on the selective area sublimation (SAS) of nanorods and nanoholes having a straight sidewall profile, achieved in a molecular beam epitaxy (MBE) chamber either from a SiN x self-organized mask 15,31 , or a SiN x nanopatterned mask 32,33 . With their conditions, nanorods and nanoholes with a high organization and fairly uniform dimensions were successfully achieved 32,33 .…”
mentioning
confidence: 99%
“…More recently, Damilano and co-authors reported several works on the selective area sublimation (SAS) of nanorods and nanoholes having a straight sidewall profile, achieved in a molecular beam epitaxy (MBE) chamber either from a SiN x self-organized mask 15,31 , or a SiN x nanopatterned mask 32,33 . With their conditions, nanorods and nanoholes with a high organization and fairly uniform dimensions were successfully achieved 32,33 . Despite the successful formation of nanoholes, few technical details have been provided on the impact of the thermal etching environment on the morphology of the nanohole arrays.…”
mentioning
confidence: 99%